Mediation of Organizational Citizenship Behavior on Non-Physical Work Environment, Organizational Culture, and Employee Performance in Steel Companies in Indonesia - Setyobudi Nugroho, Dany (Dinasti International Journal of Digital Business Management, 2025)
The purpose of this study was to examine the effect of non-physical work environment on Organizational Citizenship Behavior (OCB), the influence of organizational culture on Organizational Citizenship Behavior (OCB), the effect of non-physical work environment on employee performance, the influence of organizational culture on employee performance and the influence of Organizational Citizenship Behavior (OCB) on employee performance at Steel Company in Indonesia. The population in this study were employees of Steel Company in Indonesia. The sample size was determined using a partial least squares approach, which is 10 times the size of the formative indicators, namely the non-physical work environment with six indicators, organizational culture with six indicators plus employee performance with six indicators, for a total of 24 × 7 parameter variables, namely 168 employees. The sampling method used is a non-probability sampling technique. The results showed that the non-physical work environment had a positive and significant effect on Organizational Citizenship Behavior (OCB) and also had a positive and insignificant effect on employee performance. Organizational culture has a positive and significant effect on Organizational Citizenship Behavior (OCB) and employee performance, and Organizational Citizenship Behavior (OCB) has a positive and significant effect on employee performance.